Mannan-Specific Immunoglobulin G Antibodies in Normal Human Serum Accelerate Binding of C3 to Candida albicans via the Alternative Complement Pathway - Zhang, Mason X. (American Society for Microbiology, 1998)
Candida albicans activates the classical and alternative complement pathways, leading to deposition of opsonic complement fragments on the cell surface. Our previous studies found that antimannan immunoglobulin G (IgG) in normal human serum (NHS) allows C. albicans to initiate the classical pathway. The purpose of this study was to determine whether antimannan IgG also plays a role in initiation of the alternative pathway. Pooled NHS was rendered free of classical pathway activity by chelation of serum Ca(2+) with EGTA alone or in combination with immunoaffinity removal of antimannan antibodies. Kinetic analysis revealed a 6-min lag in detection of C3 binding to C. albicans incubated in EGTA-chelated NHS, compared to a 12-min lag in NHS that was both EGTA chelated and mannan absorbed. The 12-min lag was shortened to 6 min by addition of affinity-purified antimannan IgG. The accelerating effect of antimannan IgG on alternative pathway initiation was dose dependent and was reproduced in a complement binding reaction consisting of six purified proteins of the alternative pathway. Both Fab and F(ab′)(2) fragments of antimannan IgG facilitated alternative pathway initiation in a manner similar to that observed with intact antibody. Immunofluorescence analysis showed that addition of antimannan IgG to EGTA-chelated and mannan-absorbed serum promoted an early deposition of C3 molecules on the yeast cells but had little or no effect on distribution of the cellular sites for C3 activation. Thus, antimannan IgG antibodies play an important regulatory role in interactions between the host complement system and C. albicans.